Teacher responses to a planning framework for junior technology classes learning outside the classroom - Milne, Louise; Eames, Chris (Design and Technology Education: An International Journal, 2011)
This paper describes teacher responses to a framework designed to support teacher planning for technology. It includes a learning experience outside the classroom [LEOTC] and is designed specifically for five-year-old students. The planning framework draws together characteristics of technology education, junior primary classrooms and LEOTC to describe the role of the teacher, parent helpers and students as they work through three identified phases – preparing for a visit outside the classroom, participating in a learning experience outside the classroom, and post-visit activities in the classroom. This framework was trialled using a case study approach in two new-entrant classrooms in which students made chocolates for Mothers’ Day as part of a technology unit. Students partook in a LEOTC visit to a chocolate factory in order to examine the practice of experts before designing and making their own chocolate gift. Data sources for this paper included interviews with two participating teachers. The analysis of these suggest the use of the planning framework led to the thorough preparation of parent helpers and students, clearly defined roles for both the teachers and the parents, and the use of valuable strategies which enhanced students memories of their visit and enabled them to apply aspects of the knowledge gained to their own technological practice.